L’ecclesia, institution dominante du féodalisme : retour sur des malentendus - Joseph Morsel (L'Atelier du CRH)
Since the 1980s, a conceptual pair has increasingly structured medievalist discourse in France: dominium and ecclesia. In addition to their Latin form, these have in common the fact that they were both put into circulation by the same medievalist, Alain Guerreau, in order to account for the specific structuring of feudal society. This article focuses more particularly on the ecclesia, conceived as the dominant institution of this society. However, the use that is made of this notion is extremely variable and/or vague among medievalists, and it is therefore appropriate to return to the conditions of its formation and use. Moreover, if we admit that the ecclesia is the dominant institution of feudal society, then the double question arises of the existence and the nature of the fetishism that it implements. After having examined Alain Guerreau’s rather poorly developed propositions on this point, we will propose the hypothesis of a fetishism of holiness, even of the spiritual.